Flavones induce neutrophil apoptosis by down‐regulation of Mcl‐1 via a proteasomal‐dependent pathway. Issue 3 (29th November 2012) - Lucas, Christopher D.; Allen, Keith C.; Dorward, David A.; Hoodless, Laura J.; Melrose, Lauren A.; Marwick, John A.; Tucker, Carl S.; Haslett, Christopher; Duffin, Rodger; Rossi, Adriano G.
Abstract : Neutrophil apoptosis and subsequent nonphlogistic clearance by surrounding phagocytes are key to the successful resolution of neutrophilic inflammation, with dysregulated apoptosis reported in multiple human inflammatory diseases. Enhancing neutrophil apoptosis has proresolution and anti‐inflammatory effects in preclinical models of inflammation. Here we investigate the ability of the flavones apigenin, luteolin, and wogonin to induce neutrophil apoptosis in vitro and resolve neutrophilic inflammation in vivo. Human neutrophil apoptosis was assessed morphologically and by flow cytometry following incubation with apigenin, luteolin, and wogonin. All three flavones induced time‐ and concentration‐dependent neutrophil apoptosis (apigenin, EC50 =12.2 μM; luteolin, EC50 =14.6 μM; and wogonin, EC50 =28.9 μM). Induction of apoptosis was caspase dependent, as it was blocked by the broad‐spectrum caspase inhibitor Q‐VD‐OPh and was associated with both caspase‐3 and caspase‐9 activation. Flavone‐induced apoptosis was preceded by down‐regulation of the prosurvival protein Mcl‐1, with proteasomal inhibition preventing flavone‐induced Mcl‐1 down‐regulation and apoptosis. The flavones abrogated the survival effects of mediators that prolong neutrophil life span, including lipoteichoic acid, peptidoglycan, dexamethasone, and granulocyte‐macrophage colony stimulating factor, by driving apoptosis. Furthermore, wogonin enhanced resolution of established neutrophilic inflammation in a zebrafish model of sterile tissue injury. Wogonin‐induced resolution was dependent on apoptosis in vivo as it was blocked by caspase inhibition. Our data show that the flavones induce neutrophil apoptosis and have potential as neutrophil apoptosis‐inducing anti‐inflammatory, proresolution agents.—Lucas, C. D., Allen, K. C., Dorward, D. A., Hoodless, L. J., Melrose, L. A., Marwick, J. A., Tucker, C. S., Haslett, C., Duffin, R., Rossi, A. G. Flavones induce neutrophil apoptosis by down‐regulation of Mcl‐1 via a proteasomal‐dependent pathway. FASEB J. 27, 1084–1094 (2013). www.fasebj.org